The Impact Of Illness Perception Among People Living With Hiv: A Scoping Review - Nida; Iqbal; Hasniatisari (Jurnal Ilmiah JKA (Jurnal Kesehatan Aeromedika), 2025)
Illness perception is important and directly affects the health outcomes of people living with HIV (PLHIV). It impacts their psychological well-being, ART adherence, and quality of life. This scoping review aims to analyze the impact of illness perception among PLHIV. A literature study was conducted using Scopus, EBSCOhost, and PubMed databases with relevant keywords. Inclusion criteria included studies involving an HIV population, published in English between 2009 and 2024 and available in free full text. The result showed that negative illness perception was consistently associated with poorer quality of life, increased psychological distress, and reduced ART adherence. Conversely, interventions such as cognitive-behavioral therapy (CBT) and psychoeducation improved illness perception, leading to enhanced health outcomes. Therefore, illness perception interventions are important in HIV care strategies because they improve mental health, quality of life, and adherence to treatment, which in turn improves long-term health outcomes for people living with HIV. Keywords: illness perception, PLHIV, scoping review